ESTIMATION OF MASS TRANSFER COEFFICIENTS IN A PACKED DISTILLATION COLUMN USING BATCH MODE - A. Al-Hemiri, Adil; D. Selman, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
This research adopts the estimation of mass transfer coefficient in batch packed bed distillation column as function of physical properties, liquid to vapour molar rates ratio (L / V), relative volatility (α), ratio of vapour and liquid diffusivities (DV / DL), ratio of vapour and liquid densities (ρV / ρL), ratio of vapour and liquid viscosities (μV/ μL). The experiments are done using binary systems, (Ethanol Water), (Methanol Water), (Methanol Ethanol), (Benzene Hexane), (Benzene Toluene). Statistical program (multiple regression analysis) is used for estimating the overall mass transfer coefficient of vapour and liquid phases (KOV and KOL) in a correlation which represented the data fairly well. KOV = 3.3 * 10-10 α-0.7 (DV / DL) 0.65 (L / V) 3.5 (ρV / ρL) 1.25 (μV / μL) -5.0 KOL = 2.8 * 10-6 α-0.95 (DV / DL) 0.03 (L / V) 1.15 (ρV / ρL )0.077 (μV / μL) -0.9 In this research a method where the resistances to mass transfer in both phases are accounted for separately through the use of HTU-NTU model for each phase Z=HTUOV.NTUOV and Z=HTUOL.NTUOL Results show that both overall vapour and liquid mass transfer coefficient are increased with liquid to vapour molar rates ratio, vapour to liquid diffusivities ratio and vapor to liquid densities ratio, but decreased with increasing the relative volatility and vapour to liquid viscosities ratio.